Volume 5C: Heat Transfer 2018
DOI: 10.1115/gt2018-75099
|View full text |Cite
|
Sign up to set email alerts
|

Aerothermal Optimization of Fully Cooled Turbine Blade Tips

Abstract: Optimal turbine blade tip designs have the potential to enhance aerodynamic performance while reducing the thermal loads on one of the most vulnerable parts of the gas turbine. This paper describes a novel strategy to perform a multi-objective optimization of the tip geometry of a cooled turbine blade. The parameterization strategy generates arbitrary rim shapes around the coolant holes on the blade tip. The tip geometry performance is assessed using steady Reynolds-Averaged Navier-Stokes simulations with the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 0 publications
0
4
0
1
Order By: Relevance
“…As shown by Caloni et al [11], blade tips which combine common designs like winglet and squealer shapes with different openings can bring efficiency benefit without increase in heat load. Andreoli et al [14] showed that creating a topology free optimisation of squealer tips has a great potential in exploring different squealer topologies in single optimisation workflow. Therefore, in this work, different optimisations are carried out, gradually exploring a design space to create the novel topology free turbine tip optimisation.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…As shown by Caloni et al [11], blade tips which combine common designs like winglet and squealer shapes with different openings can bring efficiency benefit without increase in heat load. Andreoli et al [14] showed that creating a topology free optimisation of squealer tips has a great potential in exploring different squealer topologies in single optimisation workflow. Therefore, in this work, different optimisations are carried out, gradually exploring a design space to create the novel topology free turbine tip optimisation.…”
Section: Methodsmentioning
confidence: 99%
“…Comparing the squealer and carved design, authors state that squealer tips are superior to carved designs, offering larger reduction in the heat load for the price of smaller aerodynamic efficiency drop. Andreoli et al [14] did a multi-objective optimisation of turbine tips with film cooling. They parametrized geometry using mapping of the Bezier surface in non-dimensional plane which represented the blade tip.…”
Section: Previous Study On Blade Tip Aerodynamicsmentioning
confidence: 99%
“…Для уменьшения потерь вследствие утечек в радиальном зазоре применяют как активные, так и пассивные методы. Большинство опубликованных в открытых источниках методов являются пассивными и заключаются в геометрическом воздействии на структуру течения в области радиального зазора рабочей решетки ТВД: бандажирование лопаток [28][29][30], применение истираемых покрытий, применение различных форм уплотнений торцов рабочих лопаток [31] и др. Среди пассивных методов: гидростатический (например, наддув радиального зазора [32]), тепловой, механический и комбинированный.…”
Section: вихрь утечки через радиальный зазорunclassified
“…The results stated that removing the pressure side rim at the trailing edge could improve the tip cooling efficiency near the trailing edge. Andreoli et al [12] carried out the multiobjective optimization of the squealer tip rim profile. The optimized blade tip heat flux dropped by 65% and the aerodynamics efficiency increased by 0.65%.…”
Section: Introductionmentioning
confidence: 99%